Pengembangan Media Pembelajaran Snake and Ladders Culture pada Materi Indonesiaku Kaya Budaya Kelas IV SD Negeri 3 Tambaksogra - Berlian Sabrina; Agung Nugroho (Journal on Education, 2024)
A teacher's success in creating an engaging learning environment and fostering positive student attitudes is significantly influenced by various factors, including using interesting learning media. Engaging learning media can make the learning process more active and interactive. This study aims to develop and evaluate the feasibility of the Snake and Ladders Culture learning media for "Indonesiaku Kaya Budaya" of "Indonesia's Rich Cultural Heritage" for fourth-grade students at SD Negeri 3 Tambaksogra. This research employs the Research and Development (RD) methodology using the ADDIE model. Data collection methods included several questionnaires: media validation, material validation, language validation, student responses, and teacher responses. The results showed that the Snake and Ladders Culture learning media received high validation percentages: 99% by media experts (categorized as very valid), 92% by material experts (categorized as very valid), and 85% by language experts (categorized as very valid). Teacher response questionnaires yielded a percentage of 100%, and student responses were 96%, indicating that the Snake and Ladders Culture media is highly practical. The research and development results indicate that the Snake and Ladders Culture learning media is very valid and highly practical for learning.